The universe. 1 : [videorecording (DVD)] : explore the edges of the unknown - Cohen, Douglas; Thompson, Erik, 1959- (A & E Television Networks : Distributed by New Video, 2007)
Tour the surface of Earth's life-giving star. Mars may be the future of humanity - uses data collected from probes and robotic rovers. Scars on the planet's surface and in its fossil record illustrate the threat posed by meteorites, comets, and asteroids that routinely collide with Earth. Two and a half times the size of all the other planets in the solar system combined, and half a billion miles from Earth, Jupiter is a colossal riddle.